2018
DOI: 10.1016/j.jclinepi.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Measurement error and timing of predictor values for multivariable risk prediction models are poorly reported

Abstract: Reporting of measurement error and intended moment of model use is poor in prediction model studies. There is a need to identify circumstances where ignoring measurement error in prediction models is consequential and whether accounting for the error will improve the predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…Some researchers recommend that the reliability of predictor variables be explicitly evaluated, and that only those demonstrating good agreement beyond that expected by chance alone should be considered for inclusion [17]. A recent study found that measurement error of predictor variables is poorly reported, and that researchers seldom state explicitly when the predictors should be measured, and the CPR applied [140]. Another study demonstrated that predictor measurement heterogeneity across settings can have a detrimental impact on the performance of a CPR at external validation [141].…”
Section: Stages In the Development Of Clinical Prediction Rulesmentioning
confidence: 99%
“…Some researchers recommend that the reliability of predictor variables be explicitly evaluated, and that only those demonstrating good agreement beyond that expected by chance alone should be considered for inclusion [17]. A recent study found that measurement error of predictor variables is poorly reported, and that researchers seldom state explicitly when the predictors should be measured, and the CPR applied [140]. Another study demonstrated that predictor measurement heterogeneity across settings can have a detrimental impact on the performance of a CPR at external validation [141].…”
Section: Stages In the Development Of Clinical Prediction Rulesmentioning
confidence: 99%
“…By taking the measurement error perspective, our study revealed that prediction research requires consideration of variation in measurement procedures across different settings of derivation and validation, rather than analyzing the amount of measurement error within a study. A recent systematic review by Whittle and colleagues demonstrated that measurement error was not acknowledged in many prediction studies, and pointed out the need to investigate consequences of measurement error in prediction research . An important starting point for this research following from our study is that the generalizability of prediction models depends on the transportability of measurement structures.…”
Section: Discussionmentioning
confidence: 79%
“…Measurement heterogeneity within development and validation studies, for example, because of variability in measurement precision between clinicians or centers [37], is an important topic for future research. Given the potential impact and limited attention to date [38], research is needed on the effect of measurement heterogeneity for other statistical models and outcomes (e.g., survival models for time-to-event outcomes) and the impact on more flexible prediction modeling strategies. Finally, the similarity between the preferred and pragmatic measurement of a predictor was quantified using a partial correlation coefficient.…”
Section: Discussionmentioning
confidence: 99%